Disc degeneration is easily occurred at the same and adjacent cephalad level in cervical spine when Modic changes are present - Junhui Liu; Binhui Chen; Lu Hao; Zhi Shan; Yilei Chen; Fengdong Zhao (Journal of Orthopaedic Surgery and Research, 2023)
Abstract Objective This research aimed to evaluate the influence of Modic changes (MCs) on disc degeneration at the same and adjacent cephalad levels in the cervical spine. Methods This research retrospectively reviewed 1036 patients with neck pain, upper limb pain, or numbness who were treated at our out-patient clinic and underwent cervical MRI and cervical anteroposterior/lateral radiography from Jan, 2016 to Jan, 2021. MCs and disc degeneration parameters at same and nearby cephalad levels of MCs were evaluated. Discs were divided into the MCs, adjacent, and control groups, and the association between MCs and disc degeneration at the same and adjacent cephalad levels was investigated. Results Of the 1036 patients whose MRI scans were reviewed, 986 met the inclusion criteria (503 women and 483 men; average age, 62.8 years; scope of 35–79 years). The prevalence of MCs in the cervical spine was 13.0% (128/986). Type I, II, III changes were observed in 38 (29.69%), 82 (64.06%), and 8 (6.25%) patients, respectively. MCs were most frequently identified at the C5–6 (59/986; 5.98%) and C6–7 (38/986; 3.85%) levels. Disc with MCs showed worse outcomes with regard to disc degeneration grade, anterior osteophyte formation than the adjacent and control groups (p < 0.05), whereas they were more severe in the adjacent group compared to normal group. Conclusion Our findings indicate that MCs increased disc degeneration at the same and nearby cephalad levels in cervical spine, and the severity of degeneration at the same segment was more serious than that at the cephalad level.